Expression of YAP1 and pSTAT3-S727 and their prognostic value in glioma. Issue 8 (5th October 2020) - Sang, Wei; Xue, Jing; Su, Li-Ping; Gulinar, Abulajiang; Wang, Qian; Zhai, Yang-Yang; Hu, Yan-Ran; Gao, Hai-Xia; Li, Xinxia; Li, Qiao-Xing; Zhang, Wei
Abstract : Aims: A growing research demonstrated that YAP1 played important roles in gliomagenesis. We explored the expression of YAP1 and STAT3, the relationship between them and the effect of YAP1, STAT3 on prognosis in glioma. Methods: Expression of YAP1, p-YAP1, STAT3, pSTAT3-S727 and pSTAT3-Y705 in 141 cases of low-grade gliomas (LGG) and 74 cases of high-grade gliomas (HGG) of surgical specimens were measured by immunohistochemistry. Pearson's X 2 test was used to determine the correlation between immunohistochemical expressions and clinicopathological parameters. Pearson's or Spearman correlation test was used to determine the association between these proteins expression. Survival analysis was used to investigate the effect of these proteins on prognosis. Results: High expressions of YAP1, STAT3, pSTAT3-S727 and pSTAT3-Y705 were found in HGG compared with LGG (p=0.000). High expressions of YAP1, STAT3, pSTAT3-S727 and pSTAT3-Y705 were found in 63.5%, 59.5%, 66.2% and 31.1% cases of HGG, respectively. YAP1 expression was associated to tumour location, Ki-67 and P53, STAT3 expression was related with Ki-67 and P53, and the expression of pSTAT3-S727 was associated with Ki-67. There was a significantly positive correlation between YAP1 and pSTAT3-S727 (p<0.0001; r=0.5663). Survival analysis revealed that patients with YAP1 and pSTAT3-S727 coexpression had worse overall survival (OS) and progression-free survival (PFS) (p<0.0001). Tumour grade, age, Ki-67 and YAP1 expression were independent prognostic factors for OS. In LGG group, both YAP1 and pSTAT3-S727 expressions were negative correlation with IDH1 mutation, YAP1 and pSTAT3-S727 coexpression showed worse OS and PFS of glioma patients. Conclusion: Our research showed that YAP1 and STAT3 were significantly activated in HGG compared with LGG. YAP1 significantly correlated with pSTAT3-S727 in glioma, YAP1 and pSTAT3-S727 coexpression may serve as a reliable prognostic biomarker and therapeutic target for glioma.